Optimized imaging of the lower abdomen and pelvic region in hepatocyte-specific MRI: evaluation of a whole-abdomen first-pass shuttle protocol in patients with neuroendocrine neoplasms. (September 2019) - Fehrenbach, Uli; Kahn, Johannes; Fahlenkamp, Ute; Baur, Alexander; Pavel, Marianne; Geisel, Dominik; Denecke, Timm
Background: Gadoxetic acid (Gd-EOB) has shown its advantages in hepatic tumor evaluation besides its disadvantages in extrahepatic staging due to its short hemodynamic interval. This results in the dilemma of which contrast agent to choose for whole abdominal magnetic resonance imaging (MRI). Purpose: To evaluate the achievable contrast of a shuttle protocol for Gd-EOB MRI with accelerated 3D-T1-weighted sequences enabling complete dynamic liver imaging plus first-pass pelvic imaging. Material and Methods: Seventy-four patients with abdominal neuroendocrine neoplasms were scanned with a protocol including a first-pass pelvic (pelvicFP ) sequence in Gd-EOB MRI. Acquisition of this pelvicFP sequence was between portal venous and venous liver phase. Pelvic vessel and tissue enhancement was compared to a commonly acquired late/transitional phase sequence. In the same patients, liver enhancement was compared to a standard Gd-EOB protocol (n = 55) as well as to vessel contrast in previously acquired MRI with extracellular contrast medium (ECCM) (n = 14). Results: Pelvic vessel and lymph node enhancement showed significantly higher signal intensities (SI) in pelvicFP than in late phase sequences with Gd-EOB ( P < 0.001). Liver enhancement showed no significant differences compared to the standard protocol. Vessel enhancement in Gd-EOB pelvicFP showed significantly higher SI than an equilibrium phase sequence with ECCM ( P = 0.003–0.04). Conclusion: Including a pelvicFP sequence between portal venous and venous liver phases is technically feasible and achieves improved contrast in the pelvis in Gd-EOB MRI. There was no quality loss in liver enhancement compared to a regular Gd-EOB liver examination. Gd-EOB pelvicFP vessel enhancement was not inferior to an equilibrium phase with ECCM.